The community is not precarious. Sustainability and Social Capital in the Dairy Plant of the Cooperativa La Comunitaria, La Pampa, Argentina (Andamios, Revista de Investigación Social, 2025)
This paper analyzes a local development project carried out by the La Comunitaria Cooperative in General Pico, La Pampa, Argentina, which consists of a dairy plant producing cheese for local consumption. The objective is to investigate the project’s sustainability, which includes the construction of social capital, its economic dimension, and its capacity to generate employment. It also seeks to challenge a certain common sense built around the precariousness of the community. From a transdisciplinary perspective and qualitative approach, this research presents a Social and Solidarity Economy initiative that, based on a multidimensional strategy for building local power and structured within a predominantly community-based framework, successfully implemented this local development project within the cooperative-community sphere.
Keywords: Local development; sustainability; dairy plant; precariousness; social capital